How to give : an ancient guide to giving and receiving - Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D (Princeton University Press, 2020)
"Romans in the Age of Nero were preoccupied with transactional obligations, namely, what one could expect in return for something given. Emperors firmed up their power by offering donations to troops, or handouts to the public; rich men received hosts of clientelae every morning, godfather-style, promising favors or granting petitions in exchange for gifts or loyalty. Even the gods could be bought: A Roman often intoned the formula do ut des, "I give so that you may give," while making sacrifice. The Roman statesman and philosopher Seneca explored the complexities of giving and receiving in his longest ethical treatise, which goes under the title De Beneficiis. Sometimes rendered "benefit," the word beneficium denotes any gift, favor, or good turn, that is, anything that incurs (or seeks to incur) an obligation from the receiver. In this book, James Romm (translator of How to Die and How to Keep Your Cool), proposes to abridge and translate this work for modern readers under the above title. Seneca, Romm maintains, held his readers and humanity to a higher standard when it came to generosity. On his view, giving and receiving were not merely contractual matters, like business or banking, but followed higher principles of mutual care and respect. The motives behind giving, and the way it is carried out, need to be carefully examined, lest the receiver gain a boon but lose their moral standing in the process, or lest the giver exert coercive or self-serving pressures (ahem, lobbyists). He turned over every facet of the topic and used it as a way to expound larger Stoic principles regarding the interconnectedness of the human race. His aim was to urge his readers to redouble their efforts to give and receive wisely, to express gratitude when we receive a boon, and to transcend our darker, selfish impulses. In generosity, Seneca argues, lies the hope of preserving civilized life in the face of chaos"-- Provided by publisher.
Keywords: Conduct of life -- Early works to 1800.; Benevolence -- Early works to 1800.; Morale pratique -- Ouvrages avant 1800.; Bienveillance -- Ouvrages avant 1800.; PHILOSOPHY / History & Surveys / Ancient & Classical; Benevolence; Conduct of life; Latin prose style.; Latin writers.; Roman philosophy.; Seneca the Younger.; Seneca's life and times.; advice on gift giving.; anthology.; beneficia.; beneficium.; biography.; contemporary translation.; ethics.; etiquette.; favor.; gift giving.; graciousness.; gratia.; how to be gracious.; how to be grateful.; how to politely accept gifts.; how to show gratitude.; importance of generosity.; introduction to Seneca's thought.; modern translation.; new translation of Seneca.; philanthropy.; rhetoric.; rules of gift giving.; selection.; self help.; stoicism.; understanding Seneca.; writings.; Early works